2012
DOI: 10.1121/1.4756826
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling preference ratings of concert hall acoustics using subjective sensory profiles

Abstract: Subjective evaluation of acoustics was studied by recording nine concert halls with a simulated symphony orchestra on a seat 12 m from the orchestra. The recorded music was spatially reproduced for subjective listening tests and individual vocabulary profiling. In addition, the preferences of the assessors and objective parameters were gathered. The results show that concert halls were discriminated using perceptual characteristics, such as Envelopment/Loudness, Reverberance, Bassiness, Proximity, Definition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 23 publications
5
96
0
Order By: Relevance
“…Thus, the often-observed effect of slowing down of speech in a reverberant room can be understood as an adaptation that attempts to maximize the amount of information retrievable from the received signal. Similarly, basic information-theoretic considerations for the SISO channel are consistent with findings 22,23 that sufficient perceived loudness is a universally necessary condition for preference in the audition of orchestral music.…”
Section: Predictions and Assessmentsupporting
confidence: 62%
“…Thus, the often-observed effect of slowing down of speech in a reverberant room can be understood as an adaptation that attempts to maximize the amount of information retrievable from the received signal. Similarly, basic information-theoretic considerations for the SISO channel are consistent with findings 22,23 that sufficient perceived loudness is a universally necessary condition for preference in the audition of orchestral music.…”
Section: Predictions and Assessmentsupporting
confidence: 62%
“…Figure 2 illustrates example spectrograms including direct sound, reflections, and late reverberation from the first 200 ms of the impulse responses for all three surface conditions. The resulting impulse responses had similar acoustical parameters (see Table 1) to measured responses reported by Lokki et al (2012), and informal listening revealed them to be similar enough to be considered natural and realistic.…”
Section: Hall Simulationmentioning
confidence: 51%
“…Finally, the identified effect of added absorption, even at extremely short decay times may reflect on the proposed influence of passenger occupancy 3 on the reproduced sound in cars. One could infer relations of these results to previous investigations that sought to identify the perceptual aspects of sound in enclosures, e.g., studies in concert halls 28,50 and sound reproduction in small rooms. 59 A comprehensive literature review 36 suggested that the perceptual space characterizing performance spaces, sound reproduction in domestic rooms, and automotive audio seem to be heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…50 The position of Abs compared to Ref indicates a much less ambient field, less wide and enveloping, yet, a more focused sound image. This observation may relate to the decreased number of strong and dense reflections from multiple directions.…”
Section: Effect Of Absorptionmentioning
confidence: 99%